Brs3 neurons in the mouse dorsomedial hypothalamus regulate body temperature, energy expenditure, and heart rate, but not food intake. (November 2018) - Piñol, Ramón; Zahler, Sebastian; Li, Chia; Saha, Atreyi; Tan, Brandon; Škop, Vojtěch; Gavrilova, Oksana; Xiao, Cuiying; Krashes, Michael; Reitman, Marc
Abstract Bombesin-like receptor 3 (BRS3) is an orphan G-protein-coupled receptor that regulates energy homeostasis and heart rate. We report that acute activation ofBrs3 -expressing neurons in the dorsomedial hypothalamus (DMHBrs3 ) increased body temperature (Tb), brown adipose tissue temperature, energy expenditure, heart rate, and blood pressure, with no effect on food intake or physical activity. Conversely, activation ofBrs3 neurons in the paraventricular nucleus of the hypothalamus had no effect on Tb or energy expenditure, but suppressed food intake. Inhibition of DMHBrs3 neurons decreased Tb and energy expenditure, suggesting a necessary role in Tb regulation. We found that the preoptic area provides major input (excitatory and inhibitory) to DMHBrs3 neurons. Optogenetic stimulation of DMHBrs3 projections to the raphe pallidus increased Tb. Thus, DMHBrs3 →raphe pallidus neurons regulate Tb, energy expenditure, and heart rate, andBrs3 neurons in the paraventricular nucleus of the hypothalamus regulate food intake.Brs3 expression is a useful marker for delineating energy metabolism regulatory circuitry. BRS3 is a receptor regulating energy metabolism. The authors find that DMH Brs3 neurons control body temperature, energy expenditure, and heart rate, but not food intake. In contrast, PVH Brs3 neurons regulate food intake but not energy expenditure.